John D. Barrow: Pi in the Sky. Counting, Thinking and Being - Munch-Petersen, Nils Finn (Tidsskriftet Antropologi, 2019)
John D. Barrow: Pi in the Sky. Counting, Thinking and Being Anmeldes af Nils Finn Munch-Petersen